LAS AMENAZAS HÍBRIDAS COMO AMENAZA AL ESTADO (Revista de la Academia del Guerra del Ejército Ecuatoriano, 2023)
Hybrid warfare, by integrating a type of threat that integrates modern digital tools and conventional and irregular media, has put the defense system of states in check. It has gone from the classic confrontation where the armies face a threat in a conventional and symmetrical way on defined fronts, to an irregular war where the enemy is hidden in a scenery that has no limits or established rules. Hybridized threats can easily surpass the power of conventional weapons in terms of effectiveness, which will test the competencies, skills and dexterity of our soldiers considering even more that these threats will continue to constantly evolve. Our soldiers will find themselves in the need to adapt, learn and execute actions in the face of an increasingly changing reality. This article presents an analysis of the concept of hybrid threat, its background and evolution, the consequences and challenges that must be faced in this increasingly present reality.
Keywords: hybrid, threats, conventional, symmetrical, covert.